Function-Based Approach to Designing an Instructional Environment. (December 2017) - Park, Kristy; Pinkelman, Sarah
Teachers are faced with the challenge of selecting interventions that are most likely to be effective and best matched to the function of problem behavior. This article will define aspects of the instructional environment and describe a decision-making logic to select environmental variables. A summary of commonly used function-based interventions will be provided through two students: one who engages in problem behavior to access peer attention and another who engages in problem behavior to escape work tasks.